Study on the Evolution of Drainage Outlets Along Tidal Convergence Area - YUAN Cong; SUN Xiying; DING Lei; QIN Yipei; CHEN Ben (Haiyang Kaifa yu guanli)
There are different degrees of sediment scouring and silting problems in the estuaries of a large number of coastal rivers in China, which affect the demand for damp prevention, drainage and irrigation in coastal areas, as well as regional disaster prevention and mitigation and economic security. Especially in the area where tidal waves converge in the open sea, the selection of drainage outlet has always been a hot issue for engineers and scientific researchers, and it is necessary to comprehensively consider coastal tidal factors such as mean tidal range and high tide level, natural conditions such as the development of tidal channels and waterways, and the impact of human activities such as surrounding reclamation projects. Based on multi-temporal remote sensing images, the transverse oscillation characteristics of the tidal channel on the beach surface, the relationship between the migration rate and the mean tidal range, the influencing factors of the migration rate of the dichotomy beach ridge, the distance between the drainage estuary and the deep trough and the curvature of the drainage channel are obtained, and the research results can provide a basis for the planning and site selection of similar projects.